Recent discussions toward regulatory implementation of the new occupational equivalent dose limit for the lens of the eye and related studies in Japan. (3rd August 2019) - Yokoyama, Sumi; Hamada, Nobuyuki; Tsujimura, Norio
Abstract: Purpose: In 2011, the International Commission on Radiological Protection (ICRP) recommended an equivalent dose limit for the lens of the eye of 20 mSv/year, averaged over defined periods of 5 years, with no single year exceeding 50 mSv for occupational exposure in planned exposure situations. Since then, there have been extensive discussions toward regulatory implementation of such a new occupational lens dose limit. This paper provides an overview of the recent discussions toward regulatory implementation and the current status of the studies related to radiation exposure of the lens and its effect in Japan. Conclusions: In Japan, the Radiation Council established a Subcommittee in July 2017 to discuss the feasibility of implementing the new occupational lens dose limit. In March 2018, the Radiation Council requested all relevant government ministries and agencies to take necessary actions toward implementation of the new occupational lens dose limit, considering a series of discussions made by the Subcommittee. According to the currently available information, the new occupational lens dose limit (20 mSv/year, averaged over defined periods of 5 years, with no single year exceeding 50 mSv) will be implemented into regulations in Japan, most likely in April 2021, albeit subject to change. In particular, there were extensive discussions about reduction of a dose limit and radiation control for workers who may exceed 20 mSv per year, such as the Fukushima Daiichi Nuclear Power Plant decommissioning workers and medical staff, and measurement of 3 mm dose equivalent. In order to underpin regulatory practice, epidemiological and biological studies on radiation effects on the lens and studies on lens dose measurements have been conducted in Japan, some of which have been funded by the Japanese Nuclear Regulation Authority.